Asymmetric effects of economy on unemployment in Algeria: Evidence from a nonlinear ARDL approach - Mehdi Abid; Mohammed Benmeriem; Zouheyr Gheraia; Habib Sekrafi; Hanane Abdelli; Abdelhadi Meddah (Cogent Economics & Finance, 2023)
AbstractThis paper aims to establish the asymmetric effects in the short and long term of cyclical output on Algeria’s unemployment rate during the period 1970–2018. To achieve this objective, the “Okun” relation was applied, relying on a NARDL model methodology in the estimation. The main results of this study are summarized as follows. In the long run, we concluded that unemployment gap in Algeria responds in the same proportion to both recession and economic expansion (with a different signal), where the effect size reached 0,02. This shows a positive and significant effect of the unemployment gap for the last period on the current unemployment gap (where the impact size reached 0,37). In the short run, we concluded that the unemployment gap responds to recession only but does not respond to recovery. Finally, through the analysis of the dynamic multiplier effects, we concluded that the unemployment gap responds slowly to negative changes compared to positive changes in the output gap at the beginning of the period, but they converge in the long term (after 7–8 years). From a policy perspective, it follows that an increase in economic growth will not only have the desired result of reducing the overall unemployment rate, but will also have the distributional effect of reducing youth unemployment.